2007
DOI: 10.1111/j.1365-2591.2007.01217.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional evaluation of the periapical status and quality of root canal treatment in a selected population of urban Turkish adults

Abstract: The radiographic quality of root fillings correlated with periapical radiographic signs of pathosis in a selected population of Turkish adults. There is a need to improve the standards of root canal treatment in the study population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
92
8
11

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(128 citation statements)
references
References 16 publications
17
92
8
11
Order By: Relevance
“…32 Contrastly, our results showed that men are the population portion that needs more endodontic treatment (56.7%) This result can be explained with the greater interest of female patients to have dental care and their regular attendance for check-ups. 33,34 Variability exists in the literature regarding whether maxillary or mandibular teeth are most commonly treated endodontically and which tooth types are most frequently treated. 35 Our results revealed that endodontic treatment was more frequent in maxilla and maxillary teeth were more often in need of endodotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…32 Contrastly, our results showed that men are the population portion that needs more endodontic treatment (56.7%) This result can be explained with the greater interest of female patients to have dental care and their regular attendance for check-ups. 33,34 Variability exists in the literature regarding whether maxillary or mandibular teeth are most commonly treated endodontically and which tooth types are most frequently treated. 35 Our results revealed that endodontic treatment was more frequent in maxilla and maxillary teeth were more often in need of endodotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the evaluation of the quality of RF, various criteria were used in the selected studies: three studies used the distance of the endodontic filling from the root apex, 16,21,23 three studies used the filling density and its distance from the apex, 17,18,25 three studies defined the parameter as being the presence of filling material in the root canal 1,9,19 four studies preferred criteria proposed by other authors 20,22,26,27 and in one article the authors created their own guidelines 24 ( Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…In the analysis of multi root teeth by PAI, some researchers included only the highest score, 22,23,25,26 others preferred to use the lowest 1,19 and some did not mention this information. 9,[16][17][18]20,21,24,27 This difference in the diagnostic parameters is another factor that makes it difficult to compare the data between the selected articles in this present review.…”
Section: Flow Chartmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature survey indicated that most previous studies were performed among Scandinavian students and the U.S. Air Force [9,10]. In Turkey, no epidemiological research has been published regarding missing teeth, restored teeth (with either direct or indirect restoratives), implants, or impacted teeth, although two studies regarding pulp and periapical status [11,12] and one study on the mandibular cortex index of the Turkish population were reported [13].…”
Section: Introductionmentioning
confidence: 96%